Seedling descriptors and new grouping of the Tara spinosa germoplasm from the Cajamarca region, Peru. - Villena-Velásquez, Jim J. (2024)
Tara spinosa (Molina) Britton & Rose (Fabaceae), known as “tara” or “taya”, probably native to Peru, grows from sea level to 3000 m a.s.l., and is important for the tannins and gum contained in its pods and seeds, respectively. The objectives were to define and validate morphological seedling descriptors and to characterize “tara” germplasm from the Cajamarca region (58 entries from nine provinces) by integrating fruit, seed and seedling descriptors. Seven highly discriminating seedling descriptors were identified, with cotyledon descriptors being the most important. Characterization of “tara” from Cajamarca germplasm with 18 integrated descriptors (six fruit, five seed and seven seedling) allowed a new clustering, in seven groups, indicating close variability (86% duplicates).